ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP TINGKAT KEUNTUNGAN SAHAM (RETURN OF STOCK) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2012)
This journal analyzes whether the earnings per share (EPS), return on assets (ROA), affects the level of return of stock. Research methodology used in the journal companies whose shares are actively traded on the basis of trading frequency in Indonesia known as LQ-45 firms, but only limited to non-financial companies in Indonesian stock exchange. And using the model of multiple regression statistical analysis to determine the effects of independent variables on the dependent variable and the assumption of classical test equipment to see if there are irregularities in the assumption of classical test. The result of the research showed that the EPS and ROA have a significant impact partially with the level of return of stock and not the classical assumption deviation occurs after passing the normality tests.